Parameterized Modeling of Geneva Mechanism in Modular - Tong Xiaoli (Jixie chuandong)
After analyzing the current design shortcomings of Geneva mechanism,a method of Parameterized modeling for Geneva Mechanism in modular is proposed by Pro/E/layout.The method is simple,convenient and visual.It could realize fast modeling and fast reconstructing of Geneva mechanism.It provides an advice to Geneva mechanism and other mechanism design.